Are Non-Poor Households Always Less Vulnerable? The Case of Households Exposed to Protracted Civil War in Southern Sudan - Deng, L. B. (2012)
Civil wars in Africa are now the leading contributory cause of vulnerability of rural communities. Understanding vulnerability during civil war is critical for humanitarian response and post-conflict rehabilitation planning. The lack of understanding of vulnerability has led existing studies to make sweeping generalizations, either by equating the dynamics of vulnerability during civil wars with vulnerability in other risk events, or by projecting people in the 'war zones' as unable to cope and subsequently becoming vulnerable. This paper is an attempt to gain a more nuanced understanding of the dynamics of vulnerability during protracted civil war. It shows that during civil war the non-poor are not necessarily less vulnerable than poor households. The idea that people caught up in civil war are all vulnerable is not supported by the findings of this paper. It shows that the 'standard' pattern of vulnerability to drought is similar to that during exogenous counter-insurgency warfare, while a different pattern of vulnerability to endogenous shocks is identified.